ASPEK HUKUM INFORMED CONSENT DAN PERJANJIAN TERAPEUTIK - Muh Amin Dali; Warsito Kasim; Rabia Ajunu (Akademika, 2019)
(Legal Aspect Of Informed Consent And Therapeutic Agreement). Health is one of the basic rights guaranteed by the state. Therefore, the state is obliged to prepare instruments to protect the health services of citizens. In practice, one of the tools regulated by the state in guaranteeing health services is the Medical Action Agreement. In the medical world, Medical Action Approval is better known as Informed Consent. The approval of this Medical Action will be contained in a written agreement known as the Therapeutic Agreement. This study aims to analyze the legal aspects of informed consent and therapeutic agreements based on formal law in Indonesia. The scope of the discussion is the study of the relationship between the Patient Party and the Medical Personnel in the Informed Consent and Therapeutic Agreement and analysis of its formal legal aspects. The results of the study are expected to be a legal reference for the community and also the medical staff so as to increase understanding and legal awareness that lead to improving the quality of health care workers. The approach used in this study is a normative juridical approach and analytical descriptive nature. This study uses secondary data obtained from primary and secondary legal materials. The results of the study describe the analysis of the legal aspects of protecting the rights and obligations of health services for both patients and medical personnel.Kesehatan adalah salah satu hak dasar masyarakat yang dijamin oleh negara. Maka dari itulah negara berkewajiban menyiapkan perangkat-perangkat dalam melindungi hak pelayanan kesehatan warga negara. Dalam praktiknya, salah satu perangkat yang telah diatur oleh negara dalam menjamin pelayanan kesehatan adalah Persetujuan Tindakan Medis. Dalam dunia medis, Persetujuan Tindakan Medis lebih dikenal dengan istilah Informed Consent. Persetujuan Tindakan Medis ini akan dituangkan dalam perjanjian tertulis yang dikenal dengan Perjanjian Terapeutik. Penelitian ini bertujuan untuk menganalisis Aspek Hukum informed consent dan Perjanjian Terapeutik berdasarkan hukum formil di Indonesia. Ruang lingkup pembahasan adalah pada kajian mengenai hubungan antara Pihak Pasien dan Pihak Tenaga Medis dalam Informed Consent dan Perjanjian Terapeutik serta analisis aspek hukum formilnya. Hasil penelitian diharapkan dapat menjadi referensi hukum bagi masyarakat dan juga para tenaga medis sehingga dapat meningkatkan pemahaman dan kesadaran hukum yang mengarah pada peningkatan kualitas pelayan kesehatan. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif dan bersifat deskriptif analitis. Penelitian ini menggunakan data sekunder yang diperoleh dari bahan hukum primer dan sekunder. Hasil penelitian mendeskripsikan analisis aspek hukum tentang perlindungan hak dan kewajiban pelayanan kesehatan bagi pihak pasien maupun tenaga medis.